Fairness and Ethics in Spending - B. Ghassan, Hassan (Journal of Reviews on Global Economics, 2016)
Islamic faith and the ethical dimensions of the individual and the community have a significant role in guiding economic behavior by connecting the worldly life to the hereafter. In the Islamic economics paradigm, by relating ethics to the economic behavior of spending, we exhibit the good (bad) attributes of ethical (unethical) behavior. In this paper, we contribute to developing a measure of the overspending and underspending that allows testing the presence of wastefulness and niggardliness.